Exploring the effects of financial socialization and trust as it relates to financial well-being and marital satisfaction through stress and communication privacy theories - Koochel, Emily (Kansas State University, 2020)
Financial socialization, the formal and informal process of developing values, norms, knowledge, and financial behaviors (Danes, 1994), is an influential agent for how individuals interpret, compute, and communicate about finances. Using Lazarus and Folkman’s (1987) Stress and Coping theory and data from the Consumer Financial Protection Bureau’s (CFPB) National Financial Well-Being Survey, study one found evidence that stress mediates the relationship of financial skill and socialization on financial well-being, lessening the perceived threat during financial stress. Informed by Petronio’s (1991), Communication Privacy Management (CPM) theory, study two collected data on 231 individuals to explore the role of financial socialization in the development of trust. The second study found that the relationship between financial socialization and trust was mediated by financial communication. Study three explored the effect of power and trust on marital satisfaction as individuals engage in financial transparency. Findings suggest that partners’ engagement in positive financial behaviors had an effect on their perception of trust and power, which had a direct effect on marital satisfaction. Overall, these studies examined the relationship between financial socialization, communication, and finances. Findings suggest that financial socialization, a lifelong process, has an informative role when processing financial stress and attempting to harmonize financial communication. Further, findings contend that financial partnership plays a critical role in how individuals perceive power when engaging in financial transparency. Continued research to identify factors that influence communication dynamics related to finances will provide additional evidence to inform best practices for financial practitioners and educators.
Keywords: Well-being; Socialization; Stress; Communication; Transparency